Lamb weather types derived from reanalysis products. (27th April 2012) - Jones, P. D.; Harpham, C.; Briffa, K. R.
Abstract Weather typing, based on surface pressure charts, has been one of the principal means of analysis in synoptic climatology. Here, we summarize the history of manual and automated schemes, in the northwest European context, illustrating how the approaches can take advantage of the extended reanalysis products that have recently become available. The British Isles and the associated Lamb weather types (LWTs) are the focus of this study, but the approach can be applied to any mid‐to‐high latitude region to provide series back to 1871. However, caution is advised in the use of the approach where the quality and quantity of input data into the extended reanalysis are known to be temporally and spatially variable and/or poor in early years. This study intercompares the use of automated schemes with operational analyses, reanalyses and earlier manually derived LWTs. Copyright © 2012 Royal Meteorological Society